A Practical Approach to Reaction Calorimetry in Presence of Supercritical Vinylidene Fluoride. Issue 1 (December 2016) - Méndez‐Ecoscia, Ana C.; Sheibat‐Othman, Nida; McKenna, Timothy F. L.
Summary: A practical approach was implemented to follow the kinetics of the polymerization of supercritical vinylidene fluoride via emulsion polymerization using reaction calorimetry on a 4L laboratory scale reactor, in batch and semi‐batch mode. The heat flow term was studied by determining the dynamic evolution of the system under both non‐reactive and reactive conditions. Simultaneous estimations of the evolution of overall heat transfer coefficient and heat of reaction were determined using a high‐gain nonlinear cascade state estimator. Estimation strategy and hypotheses were validated by comparing the reaction rates obtained independently by calorimetry on the one hand and direct measurement of monomer consumption on the other. It was shown that while the presence of supercritical fluid in the head space led to some unexpected variation of the overall heat transfer coefficient, the method proposed here is robust enough that accurate values of the heat flow were obtained under all conditions.